Development of E-Worksheet To Improve Students’ Mathematical Problem Solving Ability: Pengembangan E-LKPD untuk Meningkatkan Kemampuan Pemecahan Masalah Matematis Peserta Didik - Mawaddah, Majdiyah; Siswanto, Rizki Dwi (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2022)
The purpose of this research is to produce learning media in the form of practical and effective student worksheets. In addition, this research is also to improve the mathematical problem solving ability of high school students in class X on the material of a three-variable system of linear equations. The method used is the R&D (Research and Development) method with a 4D model (Define, Design, Development and Disseminate). The validity test was carried out by mathematics teachers, mathematics lecturers, and media expert lecturers. The results showed that the media that had been developed based on the results of the validity test in the aspect of display quality was 94.79% in the very good category, the written text was 93.75% in the very good category, and device engineering 94.79% in the very good category. The developed media was tested practically by 10 respondents. The practicality test showed that the display quality was 99.16% in the very good category, the text results were 99.37% in the very good category, and the results of the device engineering were 100% in the very good category. The results of the students’ mathematical problem solving ability scores ranged from 75 to 100 from the results of answering e-worksheets, so that the average obtained from each student on mathematical problem-solving abilities was in the “high” category and the average percentage obtained was 94.10% in the “very good” category. Based on the results of data acquisition, it shows that the e-worksheet media on the material of a three-variable linear equation system is feasible to be used as a learning resource and can also improve students’ mathematical problem-solving abilities.